Challenges in sustaining net zero buildings in Malaysia - Nur Fadilah Darmansah; Nurakmal Abdullah; Azilah Baddiri; Siti Syariazulfa Kamaruddin; Elis Mardzianah Mazlan; Mark Cyril Francis; Ruzanah Abu Bakar (IDEAS, 2025)
Malaysia aims to achieve net zero greenhouse gas (GHG) emissions by 2050. The insufficient awareness and comprehension of the net-zero building idea among the Malaysian populace has impeded the construction sector from realising its potential advantages. According to the Global Carbon Project data, Malaysia recorded 7.63 tonnes of carbon emissions per capita. This country also lacks adequate training and expertise in the installation of innovative technologies for net-zero energy buildings. The objective of this study is to investigate the challenges related to the maintenance of net zero buildings in Malaysia. This study uses a questionnaire as a research instrument for data collection. The poll received replies from 104 civil engineers. It conducted a descriptive analysis of the obtained data, assessing the mean and frequency of respondents' agreement. The results indicate that Malaysia's workforce has the lowest average score of 2.13, signifying a deficiency in knowledge concerning the skills necessary for sustainable construction practices. In contrast, the highest mean of 4.43 indicates a positive agreement about the effective integration of Malaysia's current technology into netzero construction projects. To attain the 2050 net zero objective, stakeholders in Malaysia, including government, industry, and the public, must enhance their understanding of net zero sustainability, promote the adoption of sustainable buildings to achieve net zero, and collectively assume responsibility for environmental conservation.